The Effect of Project Based Learning and Problem Based Learning in Writing Narrative Text - Igamawati Giawa (International Journal of Educational Research Excellence (IJERE), 2022)
This study was made to find out the effect of Project Based Learning and Problem Based Learning in Writing Narrative Texts to grade XI students of SMA Swasta AL-Hikmah Medan. The researcher used experimental research. The sample of this research. The sample were 78 students of the grade XI students of SMA Swasta Al-Hikmah Medan in Academic Year 2020/2021, with population 78 students from three classes. The researcher used total random sampling technique. There were 26 students taught by using Project Based Learning method, 26 students taught by using Problem Based Learning method and 26 students as control group. The instrument used writing test to measure Project Based Learning and Problem Based Learning. The technique of data analysis is One Way Analysis of Variance (ANNOVA) with significance level p=0,21> 0,05or Fhitung=7,355 > Ftable=3.12. It was found that Project Based Learning, Problem Based Learning Methods and Control Group have different effect on students’ writing achievement of narrative texts. Project Based Learning is more effective than Problem Based Learning. Based on the results, the researchers recommended adopting the Project-Based Learning in teaching and learning situations, especially English teachers, to implement project-based learning in the teaching and learning process of writing. so that students are more active and can think critically both among students and also to teachers.